The Role of the Begawe Tradition in Strengthening Social Solidarity in the Pendua Village Community - Putri, Saskia Erlina; Haeruanisa, Haeruanisa; Sulpi, Sulpi; Suryani, Ayu Gading; Hamdani, Muh. (The Future of Education Journal, 2026)
This study aims to examine the role of the begawe tradition in strengthening social solidarity within the Pendua Village community. The research employs a qualitative method using a case study approach. Data were collected through in-depth interviews, participant observation, and documentation. The findings indicate that the begawe tradition plays a significant role in reinforcing social solidarity through various aspects, including mutual cooperation (gotong royong), social interaction, preservation of cultural values, and the enhancement of a sense of belonging within the community. The begawe tradition represents a form of local wisdom of the Sasak community in Lombok, West Nusa Tenggara, and is practiced as part of wedding ceremonies, circumcision rituals, and religious events. This tradition not only reflects the spiritual and social dimensions of the community but also strengthens communal solidarity. This study further aims to describe the forms of begawe tradition implementation, the cultural values embedded within it, and its relevance in modern community life. A descriptive qualitative method was applied through literature review and field observation. The results show that the begawe tradition continues to be preserved by the community as a symbol of cultural identity and as a means of strengthening social relationships.